3D EIT Reconstructions from Electrode Data using Direct Inversion D-bar and Calderon Methods - Hamilton, Sarah J; Isaacson, David; Kolehmainen, Ville; Muller, Peter A; Toivanen, Jussi; Bray, Patrick F (2020)
The first numerical implementation of a D-bar method in 3D using electrode data is presented. Results are compared to Calderón's method as well as more common TV and smoothness regularization-based methods. D-bar methods are based on tailor-made non-linear Fourier transforms involving the measured current and voltage data. Low-pass filtering in the non-linear Fourier domain is used to stabilize the reconstruction process. D-bar methods have shown great promise in 2D for providing robust real-time absolute and time-difference conductivity reconstructions but have yet to be used on practical electrode data in 3D, until now. Results are presented for simulated data for conductivity and permittivity with disjoint non-radially symmetric targets on spherical domains and noisy voltage data. The 3D D-bar and Calderón methods are demonstrated to provide comparable quality to their 2D CGO counterparts, and hold promise for real-time reconstructions.